Effects of Mindfulness-Based Tai Chi Chuan on Physical Performance and Cognitive Function among Cognitive Frailty Older Adults: A Six-Month Follow-Up of a Randomized Controlled Trial - Jiayuan, Z; Xiang-Zi, J; Li-Na, Meng; Jin-Wei, Y; Xue, Y (Journal of Prevention of Alzheimer's Disease, The, 2022)
AbstractBackgroundThe Objective: To assess the effectiveness of a mindfulness-based Tai Chi Chuan on physical performance and cognitive function among cognitive frailty older adults. DesignA single-blind, three-arm randomized controlled trial. SettingThree communities in Daqing, China. ParticipantsThe study sample comprised 93 men and women aged 65 years or older who were able to walk more than 10 m without helping tools, scored 0.5 on Clinical Dementia Rating (CDR) and absence of concurrent dementia, identified pre-frailty (scored 1–2 on Fried Frailty Criteria) and frailty older adults (scored 3–5 on Fried Frailty Criteria). InterventionSubjects were randomly allocated to three groups: Group1, which received mindfulness intervention (formal and informal mindfulness practices); Group 2, which received Tai-Chi Chuan intervention; Group 3, which received MTCC intervention. MeasurementsThe primary outcomes was cognitive frailty rate(measured by Fried Frailty Criteria and Clinical Dementia Rating-CDR), the secondary outcome were cognitive function (measured by Min-Mental State Examination-MMES) and physical level (measured by Short physical performance battery-SPPB, Timed up and Go test-TUG and the 30-second Chair test). They were all assessed at Time 1-baseline, Time 2-after the end of 6-month intervention and the follow up (Time 3-half year after the end of 6-month intervention). ResultsThe baseline characteristics did not differ among the groups. Improvements in the cognitive function (MMES), physical performance (SPPB, TUG, 30-second Chair test) were significantly difference between time-group interaction (p<.05). The rate of CF was significantly different among groups at 6-month follow-up period ( χ2=6.37, p<.05). A lower prevalence of frailty and better cognitive function and physical performance were found in the Group 3 compared with other two groups at the follow-up period (p<.05). ConclusionsMTCC seems to be effectively reverse CF, improving the cognitive and physical function among older adults, suggesting that MTCC is a preferably intervention option in community older adults with cognitive frailty.